The effect of food supplement programme on nutritional status of primary school children in Rural areas of Tumpat and Bachok districts - Ahmad, Zulkifli; Salleh, Halim; Hassan, Mohd Hashim Mohd (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2005)
Undernutrition is a senous global problem especially among developing countries. Undernutrition is still common among poor rural children in Malaysia. The School Supplementary Feeding Programme (SSFP) is one of the intervention strategies implemented to improve the nutritional status of children in Malaysia. The objectives of the study are to determine the prevalence of malnutrition, associated factors of underweight, stunting and wasting and to evaluate the effect of School Supplementary Feeding Programme on improving nutritional status among pnmary one children in rural areas of Tum pat and Bachok districts. The study has 2 phases. Phase 1 is a crosssectional study and the Phase 2 is a cohort study. The study was done among primary one children in rural areas of Tumpat and Bachok districts from February 2002 to March 2003. Nine hundred and thirty seven children from 18 primary schools were selected. Questionnaires eliciting socio-economic and demographic informations were answered by the parents. The weight and height of the children were measured three times; before starting SSFP, after 6 months and after 12 months of SSFP. The WAZ, HAZ and WI-IZ were calculated using Epi-Nut Antlll'opometry software (Epi Info version 6). The prevalence of malnutrition were calculated based on cutoff point of zscore < -2 SD as undernutrition and > +2 SD as overnutrition. The school administration chose eligible children to participate in the SSFP. five hundred and forty one children were enrolled in SSFP and 396 were in non-SSFP group. The prevalence of underweight~ stunting and wasting at baseline were 25 .2%, 21.1% and 6.2% respectively. Only 1.1% of children were overweight. In multiple logistic regression analysis, the significant risk factors of underweight were being male children (OR=l.4, P<O.OS), Tumpat district (OR=l .5, p<0.05) and monthly family income of R.J\1 0-250 (OR=2.2, p<0.05) and RM 251-500 (OR=2.3, p<0.05). Being a male children (OR=l.6, p<0.05) was the only significant factor for stunting and working mother (OR=2.1, p<O.OS) was the only significant factor of wasting. Repeated measures ANOV A showed there was significant different of increment of WHZ (p = 0.007) between SSFP and non SSFP group with regard to time and adjusted for gender, district, family income group and baseline nutritional status. However, no significant different of W AZ (p=O .l26) and HAZ (p=0.266) with regard to time and group was found . In conclusion, there is still a high prevalence of undernutrition among children in rural areas of Tum pat and Bachok. The condition was associated with low socio-economic and demographic status of the population. The SSFP has significantly improved the nutritional status of children with wasting. Also, the increment of W AZ, HAZ and WHZ was better among undernourished children compared to normal children.